PENGEMBANGAN MEDIA SMART STAIRS 3D PADA MATERI PENGUKURAN SATUAN PANJANG UNTUK SISWA KELAS IV SDN MANGGIS 2 - Febri Arinda; Bagus Amirul Mukmin; Elis Irmayanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by one of the difficulties faced by the fourth-grade students of SDN Manggis 2, which is the challenge of understanding the concept of length measurement units, such as conversion between kilometers, centimeters, meters, and millimeters, and difficulty in memorizing length units. This issue is caused by the use of monotonous and less interactive learning media. Based on observations from 20 students, the scores ranged from 30 to 75, and the results of a student needs survey indicated that 85% of the students expressed a strong need for learning media. Therefore, the researcher developed an innovative and engaging learning media to enhance students' understanding of length measurement units.This study aims to develop the "Smart Stairs" media as a learning aid for the material on length measurement units and to assess the validity, practicality, and effectiveness of the media product. The research used the Research and Development (R&D) method, with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The research subjects were 20 fourth-grade students. Data were collected through observations, interviews, student needs response questionnaires, pretests, posttests, as well as validation from material and media experts.The results of the study showed that the "Smart Stairs" media had a validity rate of 82.22% from the material expert, categorized as very valid, and 82.5% from the media expert, also categorized as very valid. The practicality assessment by teachers via response questionnaires obtained a score of 46, with a percentage of 83.63%, categorized as very practical. The small group trial resulted in 75.2%, categorized as practical, and the large group trial resulted in 83.9%, categorized as very practical. The learning outcome improvement showed an average pretest score of 52.25%, which increased to 85.50%, with an average improvement of 63.63%. In conclusion, the "Smart Stairs" media is suitable for use as a learning tool, as it has been proven to be valid, practical, and effective in helping students understand length measurement units.